Assessment of the Clinical Profile of Dyspepsia with Predominantly Abdominal Bloating Symptoms in Type 2 Diabetes Mellitus Patients: A Cross-sectional Observational Study - Nidhi Bhutra; Ravi Kant; Itish Patnaik; Vandana K Dhingra (Bengal Physician Journal)
Aim and background: Diabetes mellitus virtually affects every organ in the body. Gastrointestinal effects include small intestinal bacterial overgrowth (SIBO), gastrointestinal reflux disease, gastroparesis, neuropathy, pancreatopathy, and non-alcoholic fatty liver disease. Our study aimed to assess and identify various causes of dyspepsia in type 2 diabetes mellitus (DM) patients. Materials and methods: After screening the patients for inclusion and exclusion criteria, enrolled participants were subjected to a urea breath test (UBT), glucose hydrogen breath test (HBT), upper gastrointestinal endoscopy (UGIE), pancreatic fecal elastase (PEF), and gastric scintigraphy. Results: The study revealed that 42.5% of patients had positive UBT for H. pylori gastritis, while 37.5% had organic causes of dyspepsia. Pancreatic exocrine insufficiency (PEI) was present in 37.5% of patients, and slow gastric emptying in 12.5% suggested gastroparesis. There was significant negative correlation between HbA1c and pancreatic fecal elastase levels. In 26.8% of patients, no cause of dyspepsia could be identified, 34.2% had dyspepsia secondary to a single etiology; and 26.8% of patients had two underlying etiologies of dyspepsia. In contrast, the remaining had multiple causes of dyspepsia. Conclusion and clinical significance: The study identified multiple causes of dyspepsia in type 2 diabetic patients in India, with a large proportion having PEI. Further studies are needed to determine if pancreatic enzyme supplementation can alleviate dyspeptic symptoms. In conclusion, dyspepsia in diabetic patients can be attributed to multiple coexisting causes, necessitating etiology-directed management.